The role of women in the media in Kalar district (1991-2011) is a historical study - Sulaiman, Asst.L.Sabah Ali (Sulaimani Journal for Humanities, 2026)
Women have served in Kurdish society alongside men in various fields, in Garmian in general and Kalar district in particular, despite various obstacles, especially in terms of social, but women have been able to play a role in the media Their work in the field This research is based on the method of historical research (descriptive, analytical). Women journalists in Kalar district started from the beginning of the uprising (spring 1991) in the audio media and later played a role in other fields (visual and written) and worked effectively, women's rights Anfal has been reflected in the work of women journalists and they have not delayed in this regard. Through this research, it opens the door for researchers in other scientific fields to carry out various scientific works and discuss the role of women.
Keywords: Kalar District; Women Journalists; Radio Tawar; Barin Newspaper